Impact of orthogeriatric care management by orthopedic surgeons and physicians on in‐hospital clinical outcomes: A difference‐in‐difference analysis. Issue 2 (11th January 2022) - Ogawa, Takahisa; Schermann, Haggai; Khadka, Aayush; Moross, Janelle; Moriwaki, Mutsuko; Fushimi, Kiyohide; Fujiwara, Takeo; Yoshii, Toshitaka; Okawa, Atsushi; Shirasawa, Shinichi
Abstract : Aim: The orthopedic surgery unit in our suburb serves a large elderly trauma population in addition to providing elective surgeries. As patients with hip fractures have become older and at higher risk of medical complications, our hospital has initiated integrated co‐management of these patients by orthopedic surgeons and geriatricians from the point of hospital admission. The aim of this study was to evaluate the impact of the hospital policy change on hip fracture management and clinical outcome indicators. Methods: Using the difference‐in‐difference approach, in total, 288 consecutive patients with hip fractures treated during the 1 year before and 2 years after transition to orthogeriatric care from a geriatric consultation model to integrated orthogeriatric care model were compared with 576 patients from other local hospitals. Results: Despite a seasonal trend toward increased length of hospital stay in winter, the intervention significantly reduced the change in mean length of stay (mean difference [95% confidence interval], −12.9 days [−21.5 to −4.3]; P = 0.007) and discharge to home tended to change less frequently (−12.6%; P = 0.10). There was no significant reduction in mean time to surgery (−0.2 days; P = 0.83), mortality (−0.8%; P = 0.62), or complications (−1.0%; P = 0.85). Conclusions: Changing our hip fracture service from a geriatric consultation model of care to an integrated orthogeriatric model significantly reduced length of hospital stay probably due to a lower chance of discharge to home. To our knowledge, this is the first study in Japan to compare two orthogeriatric care models considering the nationwide improvement in hip fracture management. Geriatr Gerontol Int 2022; 22: 138–144 .